Battlefield to Baseball Diamond: The Niagara Parks Commission and Queenston Heights Park. (January 2014) - Young, Elaine
Abstract : Between the War of 1812's end and the late 1920s Queenston Heights was redefined from being primarily a place of memory associated with the War of 1812 to being for the most part a place of recreation. The site of a significant War of 1812 battle, until the late nineteenth century it drew growing numbers of tourists, many of whom wanted to feel closer to its wartime past. Beginning in the late nineteenth century the site's popularity for recreation increased, and by the 1920s Queenston Heights Park was a destination where thousands of people went to enjoy recreational activities such as picnics and sports. The Niagara Parks Commission, which owned the site from 1895, facilitated this transformation. The Commission saw Queenston Heights more as a park than a historic site and worked to create a recreational space that would draw tourists and increase revenue. By the 1920s the park featured attractions such as playing fields, picnic shelters, tennis courts, a restaurant, and a souvenir stand. There was little opposition to these changes, which at times jeopardized the historic landscape. Although Queenston Heights' commemorative meanings were no longer closely associated with its battlefield landscape, these meanings were increasingly invested in the imposing Brock Monument. This allowed the Commission's development of the battlefield to continue unabated, and under the Commission the landscape of the former battlefield became increasingly distanced from its wartime past.